1994
DOI: 10.2118/21710-pa
|View full text |Cite
|
Sign up to set email alerts
|

Why Scale Forms in the Oil Field and Methods To Predict It

Abstract: Summary Predicting potential scaling problems can be difficult, and numerous saturation indices and computer algorithms have been developed to determine if, when, and where scaling will occur. The Langelier, Stiff-Davis, and the Oddo-Tomson saturation indices, all widely used in the oil field, are compared and contrasted relative to calcium carbonate scale. New saturation indices for barium, strontium, and calcium sulfate scale formation are introduced and discussed, along with an updated ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
101
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(106 citation statements)
references
References 20 publications
2
101
0
3
Order By: Relevance
“…Inorganic scaling is a process of deposition of scales from aqueous solutions of minerals, referred to as brines, when they become supersaturated as a result of alteration of their thermodynamic state and chemical equilibria [13,14]. In the following section, some key terms regarding the process of calcium sulphate deposition are given.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Inorganic scaling is a process of deposition of scales from aqueous solutions of minerals, referred to as brines, when they become supersaturated as a result of alteration of their thermodynamic state and chemical equilibria [13,14]. In the following section, some key terms regarding the process of calcium sulphate deposition are given.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The variations of permeability versus pore volumes of injected fluid were measured by applying Darcy's law for single phase flow: (13) Solving Equation (13) for K yields: (14) Bu and Damsleth [20] introduced the uncertainties in permeability measurements as follows: (15) Δμ, ΔL, ΔA, ΔQ, ΔP represent the errors or uncertainties associated with these quantities. The accuracies and errors associated with the experimental equipment are given in Table 4.…”
Section: Error Analysis Of the Experimentsmentioning
confidence: 99%
“…Oddo et al (1991); Oddo and Tomson (1994) showed that the formation of calcium sulfate scale depends on temperature and does not depend on pH and can precipitate at low as well as high pH values. In the case where water injection (seawater, river, aquifer, or produced water) is used for pressure maintenance and sweep, the mixing of incompatible aqueous solutions can lead to the formation of sulfate scales when the injection water contains sulfate ions (Mackay and Jordan 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Initial electrostatic interaction of dissolved anions and cations is the genesis of ion pairs that sequentially act as "building blocks". They later assemble to form larger aggregates.…”
Section: Mechanism Of Scale Formationmentioning
confidence: 99%